Experimental research and numerical simulation of the multi-field performance of cemented paste backfill: Review and future perspectives - Wang, Yong; Wang, Zhenqi; Wu, Aixiang; Wang, Liang; Na, Qing; Cao, Chen; Yang, Gangfeng (International journal of minerals, metallurgy and materials, 2023)
Cemented paste backfill (CPB) technology is a green mining method used to control underground goaves and tailings ponds. The curing process of CPB in the stope is the product of a thermo-hydro-mechanical-chemical multi-field performance interaction. At present, research on the multi-field performance of CPB mainly includes indoor similar simulation experiments, in-situ multi-field performance monitoring experiments, multi-field performance coupling model construction of CPB, and numerical simulation of the multi-field performance of CPB. Because it is hard to study the in-situ multi-field performance of CPB in the real stope, most current research on in-situ multi-field performance adopts the numerical simulation method. By simulating the conditions of CPB in the real stope (e.g., maintenance environment, stope geometry, drainage conditions, and barricade and backfilling rates), the multi-field performance of CPB is further studied. This paper summarizes the mathematical models employed in the numerical simulation and lists the engineering application cases of numerical simulation in the in-situ multi-field performance of CPB. Finally, it proposes that the multi-field performance of CPB needs to strengthen the theoretical study of multi-field performance, form the strength design criterion based on the multi-field performance of CPB, perform a full-range numerical simulation of the multi-field performance of CPB, develop a pre-warning technology for the CPB safety of CPB, develop automatic and wireless sensors for the multi-field performance monitoring of CPB, and realize the application and popularization of CPB monitoring technology.